Proses PHK di Indonesia dengan Negara Amerika: Studi Komparasi Regulasi dan Praktik Ketenagakerjaan - Yedija Xerxes Pangaribuan (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This research presents an in-depth comparative study of the regulatory frameworks and practical applications of employment termination in Indonesia and the United States, which represent opposite ends of the labor law spectrum. Employing a normative juridical methodology with a comparative law approach, this study aims to identify philosophical differences, analyze procedural and substantive divergences, and evaluate their implications on the rights and obligations of the parties involved. The findings reveal a sharp dichotomy between the two jurisdictions. The Indonesian system adheres to a protective principle, positioning termination as a last resort (ultimum remedium). Its process is highly formalistic, requiring valid grounds strictly limited by regulation, and mandates complex procedural stages (bipartite, tripartite, up to the Industrial Relations Court) alongside strict statutory severance obligations. Conversely, the United States system is dominated by the at-will employment doctrine, which grants employers the discretion to terminate employment at any time without cause, provided it does not violate anti-discrimination laws or whistleblower protections. The U.S. process is minimalist, and financial compensation depends entirely on corporate policy or individual contracts. Conclusively, Indonesia implements a model prioritizing job security, whereas the United States emphasizes labor market flexibility. This fundamental difference carries significant implications for multinational human resource management, justice-seekers, and policymakers in reforming labor laws.